2019
DOI: 10.1096/fj.201901004r
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic leptin sensitivity and health benefits of time‐restricted feeding are dependent on the time of day in male mice

Abstract: Synchronization between biologic clocks and metabolism is crucial for most species. Here, we examined the ability of leptin, important in the control of energy metabolism, to induce leptin signaling at the molecular as well as the behavioral level throughout the 24‐h day in mice fed either a control or a high‐fat diet (HFD). Furthermore, we investigated the effects of time‐restricted feeding (TRF; a limitation of HFD access to 6 h each day) on energy metabolism during different periods throughout the 24‐h day.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 48 publications
(71 reference statements)
1
19
0
Order By: Relevance
“…Moreover, the responsiveness of HDKO mice to leptin at ZT 13 suggests that leptin sensitivity was phase-shifted rather than impaired only at ZT 1-4 in HDKO mice. This is consistent with a recent study demonstrating that DIO shifts circadian leptin sensitivity from the beginning of the light phase to the beginning of the dark phase 63 . Both SOCS3 and FABP7 deletions prevent DIO 34,64 , suggesting that their circadian repression by REV-ERBs may be an adaptative mechanism to maintain circadian leptin sensitivity on HFD.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the responsiveness of HDKO mice to leptin at ZT 13 suggests that leptin sensitivity was phase-shifted rather than impaired only at ZT 1-4 in HDKO mice. This is consistent with a recent study demonstrating that DIO shifts circadian leptin sensitivity from the beginning of the light phase to the beginning of the dark phase 63 . Both SOCS3 and FABP7 deletions prevent DIO 34,64 , suggesting that their circadian repression by REV-ERBs may be an adaptative mechanism to maintain circadian leptin sensitivity on HFD.…”
Section: Discussionsupporting
confidence: 93%
“…Simply delaying feeding time by 4 h elicits a shift in peripheral clocks and increases weight gain in mice fed HFD [ 265 ]. Thus, TRF can actually reverse the deleterious side effects of obesity [ 266 , 267 ]. Even when only adhering to TRF on the weekday and following ad libitum feeding on the weekends in HFD fed mice, the beneficial effects of TRF are still seen [ 266 , 268 ].…”
Section: The Role Of Intrinsic Clocks Of the Hypothalamus In Obesimentioning
confidence: 99%
“…In line with this, we found that DIO mice, compared to lean mice, exhibit bouts of increased basal pSTAT3 activation during the 24-hour rhythm. 68 We further demonstrated rhythmic oscillation of basal pSTAT3 activation throughout the day in DIO mice, which was independent of fluctuations in circulating leptin levels. 68 As a result of this circadian fluctuation in basal pSTAT3, dependent on timing, many studies might have missed any physiological regulation of this transcription factor by endogenous leptin because superphysiological doses of leptin lead to an abnormally high level of pSTAT3 activation.…”
Section: Lep Tin and The Centr Al Control Of Energy Homeos Ta S Ismentioning
confidence: 56%
“…68 We further demonstrated rhythmic oscillation of basal pSTAT3 activation throughout the day in DIO mice, which was independent of fluctuations in circulating leptin levels. 68 As a result of this circadian fluctuation in basal pSTAT3, dependent on timing, many studies might have missed any physiological regulation of this transcription factor by endogenous leptin because superphysiological doses of leptin lead to an abnormally high level of pSTAT3 activation. Future studies need to determine whether endogenous levels of leptin are able to regulate pSTAT3 levels within their physiological range.…”
Section: Lep Tin and The Centr Al Control Of Energy Homeos Ta S Ismentioning
confidence: 56%